Plasmodium falciparum cGMP-Dependent Protein Kinase – A Novel Chemotherapeutic Target - Rotella, David; Siekierka, John; Bhanot, Purnima (Frontiers in Microbiology, 2021)
The primary effector of cGMP signaling in Plasmodium is the cGMP-dependent protein kinase (PKG). Work in human-infective P. falciparum and rodent-infective P. berghei has provided biological validation of Plasmodium PKG as a potential drug target for treating and/or protecting against malaria. PfPKG is essential in the asexual erythrocytic and sexual cycles as well as the pre-erythrocytic cycle. Medicinal chemistry efforts, both target-based and phenotype-based, have targeted PfPKG in the past few years. This review provides a brief overview of their results and challenges.